The Effect of Internal Auditing on the Financial Performance of Small and Medium Enterprises (SMEs) in Mukono District. A Case Study of the International Medical Clinic (IMC) and Café Delish. - Andrew Guti Ilukol (Uganda Christian University, 2023)
This study was carried on “examine the contribution of internal Auditing on the financial performance of Small and Medium Enterprises? ”. The objectives of the study were to examine to establish the contributions of audit standards and professional competency of Small and Medium Enterprises, to investigate the impacts of Internal Auditing independence on the performance of Small and Medium Enterprises to find out the effects of risk management on the financial performance of Small and Medium Enterprises and to establish the effects of monitoring and controlling activities on the performance of the organizations A cross sectional research design was used, and primary data was collected to explain the research finding. The study found out that internal Auditing has various contributions towards the financial performance of Small and Medium Enterprises such as Risk management, Fraud detection which greatly contribute to the financial performance of Small and Medium Enterprises
This is a dissertation.